急性骨髄性白血病に伴い歯肉と皮膚に生じた顆粒球肉腫の1例 - 立松, 忠; 纐纈, 衆; 寺沢, 史誉; 白水, 敬昌; 文, 麻友美; 嘉悦, 淳男 (日本口腔外科学会雑誌, 2012)
Granulocytic sarcoma (GS) is a localized infiltrate of immature granulocytes in an extramedullary site. This lesion is most frequently associated with leukemia, but can occur with other myeloproliferative disorders. We report an unusual case of GS of the gingiva and skin associated with acute myelogenous leukemia. A 32-year-old man was referred to our department because of bilateral swelling of the cervical lymph nodes and gingiva accompanied by general fatigue and body weight loss. He also had a rash on the right side of the neck and right lower leg. Blood tests showed a high leukocyte count (21,370/μL), and bone marrow examination revealed acute myelogenous leukemia (French-American-British classification, M5b). We performed biopsies of the gingiva and skin lesion, and histological examination of the surgical specimen demonstrated GS. Systemic chemotherapy was initiated, and complete remission was successfully induced. The lesions of the cervical lymph nodes, gingiva, and skin disappeared after chemotherapy.